The contribution of CSR during the covid-19 period in Greece: A step forward - Kritas, Dimitrios; Tzagkarakis, Stylianos - Ioannis; Atsipoulianaki, Zoi; Sidiropoulos, Symeon (HAPSc Policy Briefs Series, 2020)
The spread of the Covid-19 brought global institutions, societies, states and economies in a critical position as they encounter a new worldwide multilevel crisis. At the same time, states have had to handle this crisis acquiring an interventionist role, protecting the social and economic cohesion, providing better health care services for their citizens and investing in scientific research, as a means to restrict this new pandemic. In order to handle that situation and its consequences, the use of all the available resources became necessary as well as the improvement of the cooperation between the private and the public sector. In Greece private sector has shown an unprecedented willingness for Greece’s CSR tradition, to contribute government’s efforts.